The Effect of Religious Moderation on Increasing Student Integrity at STIT Al-Bukhary Labuhanbatu - Dwina Putri; Suryatik, Suryatik; Elviana Sinaga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Indonesia is a country with a large population and different ethnicities, cultures and religions, with these differences it is necessary to integrate them to become a unified whole, a force capable of facing foreign cultural problems. To make this strength, you need to understand that individual differences and national differences are the nature of the Almighty. This will foster an attitude of tolerance as an embodiment of various differences; this can be realized if this nation has strong integrity in realizing concepts or words in accordance with the actions carried out. This research uses quantitative research, namely looking at the influence between variable In this research the author used a research sample of 15%. With a moderate percentage, the author assumes that the sample is representative of the research results. The sample calculation is as follows: 15% of 323 = 48.45 rounded up to 48. So the sample for this research is 48 students. This number shows that the research sample has met the research requirements. The writer determined the sample by random sampling or at random. Religious Moderation is an attitude of reducing violence or avoiding extremes in religious practices, so that religious moderation always looks for a middle way that unites and equalizes all elements in social, state and national life. Student integrity is what needs to be developed, namely physical and spiritual health, strong mental and healthy, low level of self-conflict, ability to organize one's mind, closeness to God in life, no hesitation in deciding what is right and wrong, ability to see life clearly, and able to dedicate one's duties. These characteristic aspects can be developed using several techniques, including understanding religious moderation. By increasing the characteristics of students, they will be able to transmit them to society, which can ultimately strengthen the unity and unity of the nation and state. Looking at the correlation between the Religious Moderation variable (X) and the Student Integrity variable (Y), calculations using SPSS show that the Pearson Correlation is 0.194, while the Sig. (2-tailed) 0.197, so it can be said that there is a correlation between these two variables. Furthermore, to show the influence between the independent variable and the dependent variable, calculations were obtained which showed that Sig < Research Alpha 0.034 < 0.05, meaning that the Religious Moderation variable simultaneously had a significant effect on student integrity. Next, the author draws conclusions based on the test results between variable X and variable Y. Moderation has an influence on student integrity with sig. 0.034